Hybrid minimally invasive treatment of intralobar pulmonary sequestration: a single-centre experience. (4th September 2021) - Grossi, William; Londero, Francesco; Vit, Alessandro; De Franceschi, Elisa; Masullo, Gianluca; Sponza, Massimo; Morelli, Angelo
Abstract: Pulmonary sequestrations are rare congenital malformations. They are often located in the lower lobes, and they are supplied by an aberrant systemic vessel arising from the thoracic aorta or abdominal arteries. These pulmonary malformations are divided into intra- and extralobar sequestrations, depending on the respective lack or presence of an independent pleural covering. Pulmonary sequestration can be asymptomatic or lead to recurrent pulmonary infections. The goal of this study was to analyse the feasibility and safety of a hybrid sequential approach. We report a small series of intralobar pulmonary sequestrations, from November 2017 to December 2018, successfully treated with a hybrid minimally invasive approach consisting of endovascular embolization of the aberrant arterial branch followed by video-assisted thoracoscopic lobectomy the day after. Thoracic pain following endovascular embolization was noted in all cases. Patients were discharged early in the absence of major postoperative complications. Prolonged air leak was observed in only 1 case. Despite the presence of sequestration-related pulmonary inflammation, in our experience, hybrid treatment for intralobar pulmonary sequestration is a safe and reproducible approach in terms of postoperative complications and hospital stay. Abstract : Pulmonary sequestrations (PS) are rare malformation of the lung, wherein a portion of the lung's parenchyma is supplied by an aberrant vessel arising from the thoracic or abdominal aorta.